Autoimmune hepatitis in 828 Brazilian children and adolescents: clinical and laboratory findings, histological profile, treatments, and outcomes - Gilda Porta; Elisa de Carvalho; Jorge L. Santos; Jorge Gama; Cristian V. Borges; Renata B.P.M. Seixas; Alexandre R. Ferreira; Irene K. Miura; Themis R. Silveira; Luciana R. Silva; Eleonora D.T. Fagundes; Maria A. Bellomo‐Brandao; et al. (Brazilian Society of Pediatrics, 2019)
Objective: This large study with a long‐term follow‐up aimed to evaluate the clinical presentation, laboratory findings, histological profile, treatments, and outcomes of children and adolescents with autoimmune hepatitis. Methods: The medical records of 828 children and adolescents with autoimmune hepatitis were reviewed. A questionnaire was used to collect anonymous data on clinical presentation, biochemical and histological findings, and treatments. Results: Of all patients, 89.6% had autoimmune hepatitis‐1 and 10.4% had autoimmune hepatitis‐2. The female sex was predominant in both groups. The median age at symptom onset was 111.5 (6; 210) and 53.5 (8; 165) months in the patients with autoimmune hepatitis 1 and autoimmune hepatitis‐2, respectively. Acute clinical onset was observed in 56.1% and 58.8% and insidious symptoms in 43.9% and 41.2% of the patients with autoimmune hepatitis‐1 and autoimmune hepatitis‐2, respectively. The risk of hepatic failure was 1.6‐fold higher for autoimmune hepatitis‐2. Fulminant hepatic failure occurred in 3.6% and 10.6% of the patients with autoimmune hepatitis‐1 and autoimmune hepatitis‐2, respectively; the risk was 3.1‐fold higher for autoimmune hepatitis‐2. The gamma globulin and immunoglobulin G levels were significantly higher in autoimmune hepatitis‐1, while the immunoglobulin A and C3 levels were lower in autoimmune hepatitis‐2. Cirrhosis was observed in 22.4% of the patients; biochemical remission was achieved in 76.2%. The actuarial survival rate was 93.0%. A total of 4.6% underwent liver transplantation, and 6.9% died (autoimmune hepatitis‐1: 7.5%; autoimmune hepatitis‐2: 2.4%). Conclusions: In this large clinical series of Brazilian children and adolescents, autoimmune hepatitis‐1 was more frequent, and patients with autoimmune hepatitis‐2 exhibited higher disease remission rates with earlier response to treatment. Patients with autoimmune hepatitis‐1 had a higher risk of death. Resumo: Objetivo: Este estudo com acompanhamento de longo prazo visou a avaliar o quadro clínico, os achados laboratoriais, o perfil histológico, os tratamentos e os resultados de crianças e adolescentes com hepatite autoimune. Métodos: Foram analisados os prontuários médicos de 828 crianças e adolescentes com HAI. Foi usado um questionário para coletar os dados anônimos sobre o quadro clínico, os achados bioquímicos e histológicos e os tratamentos. Resultados: De todos os pacientes, 89,6% tinham hepatite autoimune‐1 e 10,4% hepatite autoimune‐2. O sexo feminino foi predominante nos dois grupos. A idade média no início dos sintomas foi 111,5 (6; 210) e 53,5 (8; 165) meses nos pacientes com hepatite autoimune‐1 e hepatite autoimune‐2, respectivamente. Foi observado início clínico agudo em 56,1% e 58,8% e sintomas insidiosos em 43,9% e 41,2% dos pacientes com hepatite autoimune‐1 e hepatite autoimune‐2, respectivamente. A probabilidade de insuficiência hepática foi 1,6 vezes maior para hepatite autoimune‐2; 3,6% e 10,6% dos pacientes com hepatite autoimune‐1 e hepatite autoimune‐2, respectivamente, apresentaram insuficiência hepática fulminante; o risco foi 3,1 vezes maior para hepatite autoimune‐2. Os níveis de gamaglobulina e imunoglobulina G foram significativamente maiores nos pacientes com hepatite autoimune‐1, ao passo que os níveis de imunoglobulina A e C3 foram menores em pacientes com hepatite autoimune‐2; 22,4% dos pacientes apresentaram cirrose e a remissão bioquímica foi atingida em 76,2%. A taxa de sobrevida atuarial foi de 93,0%. Um total de 4,6% pacientes foram submetidos a transplante de fígado e 6,9% morreram (hepatite autoimune‐1: 7,5%; hepatite autoimune‐2: 2,4%). Conclusões: Nesta grande série clínica de crianças e adolescentes brasileiros, a hepatite autoimune‐1 foi mais frequente e os pacientes com hepatite autoimune‐2 mostraram maiores taxas de remissão da doença com respostas mais rápidas aos tratamentos. Os pacientes com hepatite autoimune‐1 apresentaram maior risco de óbito. Keywords: Autoimmune hepatitis, Clinical, Laboratory, Treatments, Outcomes, Brazil, Palavras‐chave: Hepatite autoimune, Clínico, Laboratorial, Tratamentos, Resultados, Brasil